High speed end milling of silicon using diamond coated tools with air blowing - Amin, A. K. M. Nurul; Khalid, Noor Syairah; Mohd. Nasir, Siti Nurshahida (2011)
A new method of ductile mode machining of silicon using high speed end milling with diamond coated tool and assisted by compresses air blowing has been developed. This method is capable of removing the ductile and gummy chips before they get deposited on the machined surface since gummy chips can not be removed by mechanical means once they are deposited on the surface. This method has been successful in achieving full ductile mode machining of single crystal silicon with practically no deposition of chips on the surface which has resulted in very low (0.10 μm) surface roughness values. An optimum air blowing pressure and combination of spindle speed, feed and depth of cut has been identified to achieve minimum value of surface roughness and defect free machined surface. This is an economical alternative to conventional mode of machining silicon using time consuming processes of grinding and polishing. Chemical etching can also be avoided since cutting is conducted in full ductile mode resulting in further reduction of processing time and cost.